Georgia: Country diagnostic - European Investment Bank (EIB); European Bank for Reconstruction; Development (EBRD) (European Investment Bank (EIB), 2021)
Wide-ranging reforms linked to Georgia's EU aspirations have strengthened its economy and improved living standards. Nevertheless, further reforms are still needed and the Covid-19 pandemic has had a big impact on the hospitality sector, which has been a key driving force behind the country's strong growth in recent years. To continue its economic convergence with the EU, Georgia needs to strengthen the conditions for its private sector to thrive. This report aims to identify the key challenges and opportunities for promoting private sector development and investment in Georgia. Written and researched together with the EBRD, it reviews the political and economic environment and then digs deeper into issues of public and private governance, human capital formation, gender inequalities and access to finance, particularly for SMEs. The report also looks at Georgia's external competitiveness and its infrastructure needs, with a particular focus on the energy sector in the context of climate change.
Keywords: 330; climate change; economic consequence; economic convergence; economic reform; energy market; financing; Georgia; hotel industry; infringement procedure (EU); labour market; living conditions; private education; private sector; public sector; small and medium-sized enterprises; transport infrastructure; vocational training